Report in terms of countries of the international group of companies: history and problems of formation in the context of improving the accounting system - S.F.; I.V. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The necessity of conducting research in the direction of forming the Report in terms of countries of the international group of companies has been determined. The current requirements for the formation of the Report in terms of countries of the international group of companies in Ukraine and its structure have been analyzed. The reasons and factors for the implementation of the practice of disclosure by multinational corporations of specialized reporting by country (abnormal profitability of companies, financial crisis, publication of the OECD report "Development of base erosion and profit shifting") have been analyzed. The directions of realization of the report "Development of base erosion and profit transfer" have been disclosed. The purpose of CbC reporting and its role in improving transfer pricing have been highlighted. A historical analysis of the regulatory framework for CbC reporting in Ukraine based on the use of OECD peer review reports has been conducted. The main accounting problems of implementation of the practice of forming CbC reporting have been disclosed. The consequences of the implementation of the practice of forming CbC reporting on the development of the accounting system and its ability to solve the problem of BEPS have been analyzed.